Transaxillary endoscopic subfascial operation for persistent muscular torticollis in pediatric patients: A 13-year retrospective study in Taiwan - Nai-Chen Cheng; Yu-Han Chen; Yu-Ling Wu; Yu-Tang Chang (Elsevier, 2024)
Background: The endoscopic surgery for persistent muscular torticollis has been well-described and most are subcutaneous working caverns. As the sternocleidomastoid muscle is located beneath the deep cervical fascia that corresponds to the pectoral fascia, this study aimed to review our results of the transaxillary approach under the pectoral fascia and the deep cervical fascia. Methods: Between November 2009 and January 2022, pediatric patients with persistent muscular torticollis receiving transaxillary endoscopic subfascial operation were retrospectively reviewed and analyzed. Results: There were thirty-three consecutive patients with median age of 6.5 years (range, 5.5 months-15.7 years). The median operating time was 90.0 min. With a median follow-up of 14.8 months (range, 5.0-127.7), the final outcomes showed excellent-to-good results in 90.9%, fair results in 6.1%, and poor results in 3.0%. Univariate analysis revealed that the long-term outcomes of the operation were independent of gender, age, involved side and previously open myotomy (p = 0.662, 0.818, 0.740 and 0.596, respectively). Conclusions: The subfascial working cavern would be technically achievable for the transaxillary endoscopic approach with good functional and cosmetic outcomes.